1968
DOI: 10.1042/bj1070549
|View full text |Cite
|
Sign up to set email alerts
|

The electrophoretic mobility of normal and leukaemic cells of mice

Abstract: 1. The pH–mobility relationships for saline-washed cells from a mouse strain of acute lymphoblastic leukaemia were examined before and after treatment with lower aldehydes, diazomethane and neuraminidase (EC 3.2.1.18). 2. The content of sialic acid released into the supernatant fluid of neuraminidase-treated cells was measured. 3. The stability of the charge-determining structures to temporary changes in environment (pH and ionic strength) was established. 4. Similar measurements were made on lymph-node cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
1

Year Published

1975
1975
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 18 publications
(10 reference statements)
4
19
1
Order By: Relevance
“…Similar increases in basic material have also been reported on lymph node cells derived from acute lymphoblastic leukaemia (Cook and Jacobson, 1968). Sherbet and Lakshmi (1974) demonstrated that the highly malignant astrocytomas possessed additional surface material which was basic in nature.…”
Section: Discussionsupporting
confidence: 59%
“…Similar increases in basic material have also been reported on lymph node cells derived from acute lymphoblastic leukaemia (Cook and Jacobson, 1968). Sherbet and Lakshmi (1974) demonstrated that the highly malignant astrocytomas possessed additional surface material which was basic in nature.…”
Section: Discussionsupporting
confidence: 59%
“…4 Results and discussion Figure 3 shows the experimental results of Zeta potential measurements at pH 7.4 for MCF7 cancer breast epithelial cells alone, MCF10A normal breast epithelial cells alone, iron oxide nanoparticles alone, CPMV nanoparticles alone as well as two types of cells after incubated with two different nanoparticles respectively for different time lengths of 30 min, 4 and 24 h. For MCF10A normal cells alone, the Zeta potential was −31.16±1.12 mV, which was much more negative compared to that of −20.32±2.43 mV for MCF7 cancer cells. This significant difference in surface electrokinetic properties between normal and transformed cancer cells has been reported before (Cook and Jacobson 1968). For iron oxide nanoparticles alone, the Zeta potential was −40.91± 0.14 mV indicating good dispersion stability.…”
Section: Theory and Analysismentioning
confidence: 52%
“…A few workers have already reported [Cook and J acobson, 1968;Latner andT urner. 1974: Sherbet, 1977] that the number of cationic groups on the surface of malignant cells is larger than the number present on their so-called normal counterparts.…”
Section: Discussionmentioning
confidence: 97%